(untitled) (Palíndromo, 2019)
This article features a cut-out of the work of visual artist and photographer Walter Karwatzki (Maceió/AL, Brasil, 1959). In it are evidenced three works with the technique of photography that have as platform the body of the artist. The works emphasize the passage of the photographer who used to see only the other, to the photographer who, now, sees and shows himself to the other, a change that happens due to a situation of death through which he passed. The works presented are endowed with a resulting dramaturgy of social aspects, sometimes of cultural aspects or of the artist’s personal aspects. In these works, the body is charged with a great self-referential meaning. This article presents the photographic trajectory of the author in eight photographic works that, in one way or another, have their poetic production in constant approximation with the question of memory, having as references Samain (2012), Achutti (1997, 2004), Didi -Huberman (2010), Dubois (1993), Bossi (2010), Canclini (2013) and Tolstoy (2016), among others.